Computer-aided planning for endovascular treatment of intracranial aneurysms (CAPETA) - Mohamed, Ashraf (2010)
Endovascular treatment planning of intracranial aneurysms requires accurate quantification of their geometric parameters, including the neck length, dome height and maximum diameter. Today, the geometry of intracranial aneurysms is typically quantified manually based on three-dimensional (3D) Digital Subtraction Angiography (DSA) images. Since the repeatability of manual measurements is not guaranteed and their accuracy is dependent on the experience of the treating physician, we propose a semi-automated approach for computer-aided measurement of these parameters. In particular, a tubular deformable model, initialized based on user-provided points, is first fit to the surface of the parent artery. An initial estimate of the aneurysmal segment is obtained based on differences between the two surfaces. A 3D deformable contour model is then used to localize the aneurysmal neck and to separate its dome surface from the parent artery. Finally, approaches for estimation of the clinically relevant geometric parameters are applied based on the aneurysmal neck and dome surface. Results on 19 3D DSA datasets of saccular aneurysms indicate that, for the maximum diameter, the standard deviation of the difference between the proposed approach and two independent manual sets of measurements obtained by expert readers is similar to the inter-rater standard deviation. For the neck length and dome height, the results improve considerably if we exclude datasets with high deviation from the manual measurements.